Further developments in star cluster spectral libraries - Ahumada, Andrea Veronica (2010)
We present flux-calibrated integrated spectra in the optical spectral range of galactic open clusters (GOCs) and Magellanic Cloud (MC) stellar clusters (SCs) obtained at CASLEO (Argentina). The SC parameters were derived using the equivalent-width (EW) method and the template-matching procedure by comparing the line strengths and continuum distribution of the cluster spectra with those of template spectra with known parameters. MC cluster reddening values were also estimated by interpolation between the available extinction maps. The derived ages for the GOCs range from 3 Myr to 4 Gyr, while those of the MC SCs vary from 3 Myr to 7 Gyr. E(B − V ) colour-excess values in the MCs appear to be all lower than 0.17 mag, while those of the GOCs range from 0.00 to 2.40 mag. The present data led us to upgrade the spectral libraries of reference spectra or templates of solar and MC metallicities.